2021
DOI: 10.18502/htaa.v5i1.7377
|View full text |Cite
|
Sign up to set email alerts
|

The Importance-Performance Analysis of the Quality of Services Provided for Patients in Hospitals Affiliated to Ahvaz Jundishapur University of Medical Science

Abstract: Background: Quality is a key factor in the distinction of services, and it is a potential source of sustainable competitive advantage to increase productiveness and patient satisfaction. The identification of strengths and weaknesses in quality of provided services can help to recognize priorities and develop improvement strategies. Objectives: Using importance-performance analysis (IPA) method, this study aimed to evaluate the quality of services provided in hospitals affiliated to Ahvaz Jundishapur Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…This acknowledgment underscores the recognition that achieving ideal conditions is often a complex and multifaceted endeavor, subject to various real-world constraints and limitations. Although this study found a significant negative gap, compared to other studies in healthcare settings in several countries such as Brazil 11 and Iran, 10 , 13 , 19 the findings of this study are better. This indicates that the University Health Center offers a commendable service compared to international providers.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…This acknowledgment underscores the recognition that achieving ideal conditions is often a complex and multifaceted endeavor, subject to various real-world constraints and limitations. Although this study found a significant negative gap, compared to other studies in healthcare settings in several countries such as Brazil 11 and Iran, 10 , 13 , 19 the findings of this study are better. This indicates that the University Health Center offers a commendable service compared to international providers.…”
Section: Discussioncontrasting
confidence: 90%
“… 11 Combining customer ratings from Performance and Importance provided an overall view of satisfaction and clear direction for management regarding where to focus their resources. 13 , 18 , 19 The IPA methodology involves the comparison of an ideal value with the existing reality, providing a mechanism for assessing the alignment or disparity between theoretical ideals and practical outcomes. The IPA method has several advantages, such as being easy to administer, efficient, and applicable to various fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPA matrix in the form of an IPA Cartesian diagram was divided into four quadrants, which were bounded by two axes that intersect perpendicularly at point ( x , y ), where the P means were the x -axis and the E means were on the y -axis. The items could then be analysed based on resource allocation priorities ( 8 , 12 , 18 ). The IPA matrix was created and analysed using the Statistical Package for Social Sciences (SPSS) version 23.0 (USA).…”
Section: Methodsmentioning
confidence: 99%
“…The IPA method is a reliable analytical tool for practitioners and academics, and it finds attributes that require corrective action. IPA allows hospital management and other health services to understand patient perceptions and expectations ( 8 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%